2007
DOI: 10.1029/2006je002815
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor diffusion in Mars subsurface environments

Abstract: The diffusion coefficient of water vapor in unconsolidated porous media is measured for various soil simulants at Mars‐like pressures and subzero temperatures. An experimental chamber which simultaneously reproduces a low‐pressure, low‐temperature, and low‐humidity environment is used to monitor water flux from an ice source through a porous diffusion barrier. Experiments are performed on four types of simulants: 40–70 μm glass beads, sintered glass filter disks, 1–3 μm dust (both loose and packed), and JSC Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 82 publications
4
93
1
Order By: Relevance
“…Other forces influence vapor transport, including osmotic pressure and nonisothermal vapor flux; but it has been reported that Fickian diffusion processes dominate transport in extreme cold environments (Chevrier et al, 2007(Chevrier et al, , 2008Hudson et al, 2007). Our vapor-diffusion model ignores the very minor effects of Knudsen diffusion and does not specifically track vapor density beyond saturation (as may occur with the formation of hoar frost).…”
Section: Assumptions and Model Formatmentioning
confidence: 95%
“…Other forces influence vapor transport, including osmotic pressure and nonisothermal vapor flux; but it has been reported that Fickian diffusion processes dominate transport in extreme cold environments (Chevrier et al, 2007(Chevrier et al, , 2008Hudson et al, 2007). Our vapor-diffusion model ignores the very minor effects of Knudsen diffusion and does not specifically track vapor density beyond saturation (as may occur with the formation of hoar frost).…”
Section: Assumptions and Model Formatmentioning
confidence: 95%
“…From 2 to 75 mm, the sublimation rate should decrease by a factor ∼38 (see Section 4.1), while the temperature difference generates an Fig. 2), as a function of surface temperature for a variety of clay depths, L. The data lie below the theoretical (Ingersoll, 1970) and experimental (Moore and Sears, 2006) curve for water ice sublimation. Sublimation rate decreases with regolith thickness.…”
Section: Temperature Dependence Of Sublimation Ratementioning
confidence: 95%
“…Mars is known to have buried ice within its subsurface 20 and water vapour can be transported by diffusion to the surface 12 . Ref.…”
mentioning
confidence: 99%